Membaca Ekspresi Kontestasi Gerakan Perempuan Melawan Industrialisasi di Kawasan Pegunungan Utara Jawa, Indonesia - Setiadi Setiadi; Nur Rosyid (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2021)
This study examines the intertwining of the attributive elements of feminine narrative on social movement in relation to the narration of Gegeran (riot) Samin in the context of industrialization in Kendeng, Central Java. Recent studies accentuated the narration of Saminisme as the history of resistance to colonialism becomes a study of the description of an unpretentious culture that is to be relevant for cultural conservation. Meanwhile, during this tumultuous era of industrialization, the reconstruction of the narrative of Saminism as a resistance movement was again in the spotlight, especially why women seemed dominant in this struggle. This research was conducted in April-May 2016 based on a narrative ethnography approach that is to be more sensitive to the emergence of a story, between textual and contextual data. The question was why there are differences in the articulation of narratives between elements of Sedulur Sikep values in responding to the establishment of cement factory reflected in the different attitudes and expressions. The research concludes that this social movement is intertwined with struggle efforts based on awareness of cultural diversity and socio-economic class movements by elaborating narrative elements from the specific historical narrative as the cyclical mobilization and are constituted using the performative elements of the activities or actions they held